Pengembangan Komik Digital Huruf Jawa pada Mata Pelajaran Bahasa Jawa Kelas VII di SMP Negeri 29 Surabaya - Retno Danu Rusmawati; Nunung Nurjati; Suharti Suharti (Tafhim Al-'Ilmi, 2022)
AbstractJava script digital comic media was developed with the aim of: producing appropriate Javanese script digital comic media in Javanese language learning for class VII SMP Negeri 29 Surabaya, getting new experiences in learning and providing a positive influence on students, namely by increasing student learning outcomes, making it easier for teachers to implement learning, especially for the material Java letters. In this study, researchers used research and development methods or better known as Research and Development. Research and development methods are research methods used to produce certain products, and test the effectiveness of these products. The research used is a needs analysis and to test the effectiveness of the product so that it can function in the wider community. In this study, researchers developed a Javanese script digital comic media for even semester VII graders. The test subjects for digital comic media were 20 students of SMP Negeri 29 Surabaya in class VII. Data analysis is divided into two types, namely qualitative data analysis and quantitative data analysis. This development research uses Dick & Carey development with ten steps of development, namely, identification of learning objectives, learning analysis, learner analysis and context, determining learning objectives, developing assessment instruments, learning strategies, selecting learning materials, designing and conducting formative evaluations, revising and designing and conduct a summative evaluation. By following these ten steps, it can be concluded that the development of Javanese script digital comic media in Javanese language subjects at SMP Negeri 29 Surabaya for class VII students with the Dick and Carey development model is said to be feasible to be applied in the learning process of Javanese language subjects. Keywords: Digital Comics, learning development, Javanese language